Psychophysical interpretation for utility measures - Yuqing He (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
The paper explores utility measures by combining experiments with mathematical derivations in the psychophysics paradigm. The analysis on the ultimatum game experiment reveals evidences for the utility threshold and thus supports Bernoulli's utility logarithmic law. Both experimental results and theoretical derivations show that the logarithmic law is suitable for the description of commodity choice and the power law for risk choice. The further mathematical demonstration indicates the logarithmic law for utility scaling to be a KleinRubin utility function, a utility function well defined in microeconomics. Based on this, the experimental utility measure is connected with the econometric model Linear Expenditure System, and presents an experimental procedure for testing the utility maximization hypothesis, which will resolve a long unsettled perplexity in a fundamental stone of economics since Gossen proposed it in 1854.
Keywords: A12; D01; 330; psychophysics; ultimatum game; utility function; logarithmic law; power law; Nutzen; Ultimatumspiel; Wirtschaftspsychologie; Nachfragesystem; Theorie